An evaluation of rehabilitation students’ learning goals in their first year: a text mining approach - Kitamura, Shin; Takeda, Kotaro; Uehara, Shintaro; Yoshida, Taiki; Ota, Hirofumi; Tanabe, Shigeo; Takeda, Kazuya; Koyama, Soichiro; Sakurai, Hiroaki; Kanada, Yoshikiyo (Frontiers in Medicine, 2024)
Introduction Qualitative information in the form of written reflection reports is vital for evaluating students’ progress in education. As a pilot study, we used text mining, which analyzes qualitative information with quantitative features, to investigate how rehabilitation students’ goals change during their first year at university. Methods We recruited 109 first-year students (66 physical therapy and 43 occupational therapy students) enrolled in a university rehabilitation course. These students completed an open-ended questionnaire about their learning goals at the time of admission and at 6 and 12 months after admission to the university. Text mining was used to objectively interpret the descriptive text data from all three-time points to extract frequently occurring nouns at once. Then, hierarchical cluster analysis was performed to generate clusters. The number of students who mentioned at least one noun in each cluster was counted and the percentages of students in each cluster were compared for the three periods using Cochran’s Q test. Results The 31 nouns that appeared 10 or more times in the 427 sentences were classified into three clusters: “Socializing,” “Practical Training,” and “Classroom Learning.” The percentage of students in all three clusters showed significant differences across the time periods (p < 0.001 for “Socializing”; p < 0.01 for “Practical Training” and “Classroom Learning”). Conclusion These findings suggest that the students’ learning goals changed during their first year of education. This objective analytical method will enable researchers to examine transitional trends in students’ reflections and capture their psychological changes, making it a useful tool in educational research.